Answer:
(1,2)
Explanation:
Eliminate y-term
![(x + 2x) + (4y - 4y) = 9 - 6 \\ 3x = 3 \\ x = (3)/(3) \\ x = 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/khs5d2o1jt8rwwi92cp49lmzv97yrxcw0k.png)
Substitute x = 1 in any given equations.
I choose to substitute in the first equation.
![x + 4y = 9 \\ 1 + 4y = 9 \\ 4y = 9 - 1 \\ 4y = 8 \\ y = (8)/(4) \\ y = 2](https://img.qammunity.org/2022/formulas/mathematics/high-school/kpr80xb1hgqc6iha7r8eggkxs2nsucoyzj.png)
Answer Check
Substitute both x-value and y-value in any given equations.
![x + 4y = 9 \\ 1 + 4(2) = 9 \\ 1 + 8 = 9 \\ 9 = 9](https://img.qammunity.org/2022/formulas/mathematics/high-school/y6cg3otr2dibmfxirt4o0m3h9gya6nzjn5.png)
The first equation is true. However, we have to check the second equation as well. (Although the first true equarion has already raised the high possibility of right answer.)
![2x - 4y = - 6 \\ 2(1) - 4(2) = - 6 \\ 2 - 8 = - 6 \\ - 6 = - 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/e1owgapsjmctxhf2c4073u6crjp72jrq4m.png)
Both equations are true for (1,2). Thus the answer is (1,2)